1984
DOI: 10.1210/jcem-58-5-838
|View full text |Cite
|
Sign up to set email alerts
|

Human Pancreatic Tumor Growth Hormone-Releasing Factor: Dose-Response Relationships in Normal Man*

Abstract: Human pancreatic GRF (hpGRF-40; 1 microgram/kg, iv) selectively stimulates GH release in normal men (9). We now report the effects of graded doses of hpGRF-40 on GH release in 12 normal men. Mean peak increments in serum GH after vehicle and the various doses of hpGRF-40 were 1.13, 11.40, 14.60, 17.01, 14.45, and 15.60 ng/ml after vehicle and 0.1, 0.33, 1.0, 3.3, and 10 micrograms/kg hpGRF-40 (iv bolus), respectively. Peak values were observed 30-60 min after hpGRF-40 treatment. There was considerable variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(38 citation statements)
references
References 18 publications
3
35
0
Order By: Relevance
“…It should be noted that the subjects assigned to experiment 1 and experiment 2 were different. Considerable variabilities in GH responsiveness to GHRH among individual subjects in normal men (25,26) and acromegaly (27) have been reported. Therefore, different GH responses to GHRH seen in this study were considered within the normal range.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the subjects assigned to experiment 1 and experiment 2 were different. Considerable variabilities in GH responsiveness to GHRH among individual subjects in normal men (25,26) and acromegaly (27) have been reported. Therefore, different GH responses to GHRH seen in this study were considered within the normal range.…”
Section: Resultsmentioning
confidence: 99%
“…GHRH stimulation has therefore been advocated as a physiological test of pituitary somatotroph reserve and as a potential tool for the evaluation of clinical disorders of growth (4)(5)(6). The usefulness of this test, however, has been limited by the marked variability in the amplitude of the responses (1, 7,8). The range of GH responses in normal subjects varies from very brisk to barely detectable, a far greater variability than that observed with administration of any other hypothalamic releasing factor.…”
mentioning
confidence: 99%
“…specifically stimulates G H release in normal men (3)(4)(5) and it has been shown that increases in circulating concentrations of ir-GHRH are followed by GH release in some physiologic situations (6,7). However, only a little is known about the role of GHRH in the generation of the nocturnal rhythm of GH secretion.…”
mentioning
confidence: 99%